Hindsight bias an interaction of automatic and motivational factors? - Hell, Wolfgang; Gigerenzer, Gerd; Gauggel, Siegfried; Mall, Maria; Miller, Michael (Psychonomic Society, 1988)
If subjects are asked to recollect a former response after having been informed about the correct response, their recollection tends to approach the correct response. This effect has been termed hindsight bias. We studied hindsight bias in an experiment requiring numerical responses to almanac-type questions for physical quantities. We varied (l) the time at which the correct information was provided, (2)the encoding of the original responses by asking/not asking subjects to give a reason for the respective response, and (3)the motivation to recall correctly. We found that hindsight is less biased if reasons are given and if the correct information is provided at an earlier time. Motivation had only interactive effects: (1)With high motivation to recall correctly, the time the correct information was provided had no influence. (2)With reasons given, the variation of motivation showed no effect. These results rule out purely motivational and purely automatic explanations.